A code theory perspective on science access: Clashes and conflicts - Ellery, K. (South African Journal of Higher Education, 2017)
Quantitative measures of student performance fail to provide insight into underpinning constraints and enablements to access in science in higher education. This case study of a science foundation course uses Legitimation Code Theory as a theoretical frame and acquisition of recognition and realisation rules as an analytical frame to provide a depth empirical account of student access and success. Results indicate that access to the powerful science knowledge in the epistemic context is dependent on students recognising and realising the knower code of the learning context, which requires of them to be independent and autonomous learners. Such access is not afforded when students prior (school) learning-context relativist code clashes with the required university learning-context knower code. It is argued that a focus on the learning context could be key in enabling access to students whose educational background does not align well with that of the higher education context.